Differential Response of Azolla-Anabaena Associations to High Temperature and Minus Phosphorus Treatments - Tung, H.F.; Watanabe, I. (Wiley, 1983)
The response of Azolla species to high temperature and minus phosphorus (– P) treatments was investigated. Azolla filiculoides was judged the most sensitive to high temperature on the basis of its growth, acetylene reduction activity (ARA), losses in chlorophyll and protein content. The temperature‐tolerant strains like A. pinnata (Cheng Mai and Pu Tiang Zhu) and A. microphylla showed good growth and no senescence even after 6 weeks at 37/29°C provided that plant density was controlled and nutrients were not limiting.The – P treatment reduced both growth and N2‐fixation in the Azolla plants. Its effect was greater on N2‐fixation as measured by ARA, than on growth in the first week of culture in a P‐deficient medium. High temperature did not hasten or enhance the appearance of P deficiency symptoms. A lower endogenous P content was needed to induce physiological disorder in A. pinnata than in A. mexicana and A. microphylla.